The correlation between quorum sensing genes (pqsR and lasR) in antibiotic resistance of Pseudomonas aeruginosa isolated from burned patients - Bahrami, Nikou; Mohammadi, Mehrdad; Sabzi, Niloofar; Ghanei, Maryam (Archives of Medical Laboratory Sciences, 2020)
Background: Pseudomonas aeruginosa, a gram-negative bacillus, and opportunistic pathogen, is an important microorganism involved with infections in burn patients worldwide. It produces biofilms by Quorum-sensing signals and makes an antibiotic resistance. Materials and Methods: From April to September 2018, 100 samples of burn injuries were collected from the Central Hospital of Shahid Beheshti in Kashan. The samples were identified in terms of biochemical and phenotypic tests and a definitive diagnosis of P.aeruginosa species was examined based on a toxA gene by the PCR method. The positive samples were analyzed for antibiotics of amikacin, ciprofloxacin, norfloxacin, gentamicin, cefepime, aztreonam, meropenem, ceftazidime, colistin, and piperacillin-tazobactam. Then, samples were analyzed for lasR and pqsR (quorum-sensing genes) by PCR. Results: We verified eighty-five (85%) isolates as P. aeruginosa. According to antibiograms, 92% of the isolates were considered as multidrug-resistant (MDR), of which 85.5% were extensively drug-resistant (XDR) and none of the pan drug resistance (PDR). Also, in MDR isolates, there was one nonsense mutation. In XDR samples, two isolates had a missense mutation and nonsense mutation was seen in one strain. Conclusion: The results of our study show that with increasing resistance rates, more mutations occur in lasR and pqsR genes and the possibly can play a key role in antibiotic resistance. Given the mutations found in the quorum sensing genes, it can be concluded that these genes are mutagenic genes that will be effective in changing bacterial behavior and adaptability to environmental conditions.